2010
DOI: 10.1016/j.micres.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel glucansucrase from Leuconostoc lactis EG001

Abstract: A gene encoding glucansucrase was identified in Leuconostoc lactis EG001 isolated from lactic acid bacteria (LAB) in Kimchi, a traditional Korean fermented food. The L. lactis EG001 glucansucrase gene consists of 4503 bp open reading frame (ORF) and encodes an enzyme of 1500 amino acids with an apparent molecular mass of 165 kDa. The deduced amino-acid sequence showed the highest amino-acid sequence identity (75%) to that of dextransucrase of L. mesenteroides. The gene was cloned and over-expressed in Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Complete genome sequence of L. mesenteroides ATCC 8293 (GenBank no. NC_008531), a strain equivalent to KCTC 3718 [29], was used as a reference sequence to detect genetic alterations. Conventional PCR and Sanger sequencing service (Macrogen, Korea) were used to confirm the sequence changes observed after Illumina sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Complete genome sequence of L. mesenteroides ATCC 8293 (GenBank no. NC_008531), a strain equivalent to KCTC 3718 [29], was used as a reference sequence to detect genetic alterations. Conventional PCR and Sanger sequencing service (Macrogen, Korea) were used to confirm the sequence changes observed after Illumina sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Glucansucrase enzymes are interesting biocatalysts for the glycosylation of small organic molecules, because they are promiscuous towards a wide range of acceptor substrates (Monsan et al 2010; Leemhuis et al 2012). Using inexpensive sucrose as glycosyl donor, glucansucrase enzymes glucosylate, for instance, phenolic compounds such as catechol (Meulenbeld and Hartmans 2000; Devlamynck et al 2016; te Poele et al 2016) and hydroquinone (Seo et al 2009; Devlamynck et al 2016), primary alcohols (Seibel et al 2006; Devlamynck et al 2016), and l -ascorbic acid (Kim et al 2010). Glycosylation may change the physico-chemical and biological properties of molecules, enhance bioavailability of antibiotics, or improve stability of molecules against auto-oxidation (Desmet et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This research demonstrated that up to 0.3% β-glucan could be added to yogurt, which meets the nutrient guidelines for added nutritional benefits, without affecting the characteristics of yogurt significantly. The solidification of milk using glucansucrase produced by Leuconostoc species was previously observed by Kim et al [18,19] when the W. hellenica SKKimchi3 strain and Lac. lactis EG001 were cultivated in an MRS medium where 10% sucrose was added to skim milk.…”
Section: Application Of the Dsrlm34 For The Solidification Of Sucrosementioning
confidence: 63%
“…lactis EG001, showing a difference of 30 amino acids from the EG001 glucansucrase amino acid sequence (Fig. 2) [19].…”
Section: Cloning and Nucleotide Sequence Determination Of Glucansucrasementioning
confidence: 99%
See 1 more Smart Citation